Review of the advisory role of the international court of justice - Ganić Senad (Međunarodni Problemi, 2010)
This paper presents a brief review and analysis of advisory proceedings before the International Court of Justice as well as an explanation of the nature and importance of advisory opinions as specific decisions of the International Court of Justice. The intention was to make the public more familiar with the nature of these proceedings drawing attention of the professional public to some specific elements that characterize advisory procedures, which in a sense make them closer to the proceedings in resolving disputes between states. Although not binding by their nature as are decisions of the Court, advisory opinions have, however, some weight and importance that primarily stem from the importance and authority of the body that provides them. A non-binding effect of advisory opinions is just a starting point in explaining them. Actually, it is the fact that opinions have a great authority and this requires some further explanations.